Successful Management of a Patient With Jacobsen Syndrome and Hypoplastic Left Heart Syndrome. Issue 3 (May 2021) - Herrick, Nicole L.; Lamberti, John; Grossfeld, Paul; Murthy, Raghav
Jacobsen syndrome (JS) is a rare genetic condition characterized by intellectual disability, hematologic abnormalities, and congenital heart defects. A male infant presented at birth with phenotypic findings of JS and echocardiographic findings of hypoplastic left heart syndrome (HLHS). Array comparative genomic hybridization was performed at age three days and revealed an 8.1 Mb terminal deletion on the long arm of chromosome 11, consistent with JS. At five days of age, a hybrid stage 1 procedure was performed. At age 46 days, he underwent a Norwood operation followed by bidirectional Glenn at age six months. He is presently 23 months old and doing well. With careful consideration of the individual patient and comorbidities associated with JS, we propose that at least a subset of patients with JS and HLHS can do well with staged surgical palliation.